MobiQiyas: A Mobile Learning Standardized Test Preparation for Saudi Arabian Students - Alabbadi, Mohssen Mohammed (International Journal of Interactive Mobile Technologies (iJIM), 2010)
A mobile learning system, called MobiQiyas, for preparing Saudi Arabian students for one of the standardized tests, given by the National Center for Assessment in Higher Education (NCAHE), has been developed, using ready-made commercial products and tools. The learning material of MobiQiyas consists of practice questions with their answers, both provided by NCAHE, to be loaded by the students into their own mobile phones; after installation, the students can interact with MobiQiyas any number of times, as desired, without incurring any additional cost, other than the initial airtime cost for downloading. From total number of students taken the test, 20,000 students were randomly selected to use MobiQiyas and information was collected from them to measure their attitudes and participation of MobiQiyas. It was found that 36.1% of students had actually downloaded MobiQiyas successfully. Furthermore, a telephone survey was conducted, after the test period, on a class of 40 students in a secondary school in Riyadh, taking the same test, to measure their acceptance of MobiQiyas, using a 9-item questionnaire based on a 5-point Likert scale. The responses of the 40 students reflected high acceptance and satisfaction levels of MobiQiyas as an effective test prep tool.